Isomerization and Redox Tuning: Reorganizing the Maya Blue Puzzle from Synthetic, Spectral, and Electrochemical Issues - Doménech-Carbó, Antonio; Costero, Ana María; Gil, Salvador; Montoya, Noemí; López-Carrasco, Alejandro; Sáez, José A.; Arroyo, Pau; Doménech-Carbó, María Teresa (American Chemical Society, 2022)
A new approach to describe the composition of Maya blue (MB), an ancient organic-inorganic hybrid material, is presented. It is based on the analysis of attenuated total reflection-Fourier transform infrared (ATR-FTIR), Raman spectroscopy, UV-visible (vis) spectroscopic, and electrochemical data for indigo and dehydroindigo plus palygorskite hybrids, including a novel methodology using electrocatalytic effects on the oxygen reduction reaction. As a result, it is concluded that MB results from the tautomerization of indigo-to-indigo hemienol and the subsequent oxidation of these isomeric forms to dehydroindigo, all associated with the palygorskite clay framework, at temperatures above 100 °C. This model is also consistent with13C NMR data on indigo plus sepiolite hybrids. A consistent set of thermochemical parameters is obtained from ATR-FTIR, solid-state electrochemistry, and UV-vis diffuse reflectance spectra for the successive isomerization and redox tuning processes experienced by palygorskite-associated indigo.
Keywords: electrochemistry; electrolytic reduction; isomerization; isomers; organic-inorganic materials; spectroscopic analysis; supersaturation; tuning; Scopus; WOS(2)